Meta Analysis of Factors Associated with Job Satisfaction in Health Workers - Hapsari, Fara Rizky Punjung; Murti, Bhisma; Tamtomo, Didik (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Job satisfaction is a perception that is reflected in attitude and focused on behavior towards a job, and is a form of human interaction with the work environment. High job satisfaction is a sign that an agency has done good management. The more satisfied the health workers in an institution, the more maximum their level of performance and productivity so that the goals of the institution can be achieved. The study aims to analyze the factors that affect job satisfaction in health workers based on the results of previous similar studies. Subjects and Method: It was a systematic review and meta-analysis study with the PICO as follows: P = health workers, I = high salary, the availability of supervision C = low salary, no supervision O = job satisfaction. The data collection was conducted through the databases, namely: Google Scholar and PubMed. The inclusion criteria used were full English papers with Cross Sectional designs in 2012-2022. The keywords used were “job satisfaction